Optimizing PEEK implant surfaces for improved stability and biocompatibility through sandblasting and the platinum coating approach - Faadhila, Afrah; Taufiqurrakhman, Mohamad; Katili, Puspita Anggraini; Rahman, Siti Fauziyah; Lestari, Delly Chipta; Whulanza, Yudan (Frontiers in Mechanical Engineering, 2024)
Polyether–ether–ketone (PEEK) is a commonly employed biomaterial for spinal, cranial, and dental implant applications due to its mechanical properties, bio-stability, and radiolucency, especially when compared to metal alloys. However, its biologically inert behavior poses a substantial challenge in osseointegration between host bone and PEEK implants, resulting in implant loosening. Previous studies identified PEEK surface modification methods that prove beneficial in enhancing implant stability and supporting cell growth, but simultaneously, those modifications have the potential to promote bacterial attachment. In this study, sandblasting and sputter coating are performed to address the aforementioned issues as preclinical work. The aim is to investigate the effects of surface roughness through alumina sandblasting and a platinum (Pt) sputtered coating on the surface friction, cell viability, and bacterial adhesion rates of PEEK material. This study reveals that a higher average surface roughness of the PEEK sample (the highest was 1.2 μm obtained after sandblasting) increases the coefficient of friction, which was 0.25 compared to the untreated PEEK of 0.14, indicating better stability performance but also increased bacterial adhesion. A novelty of this study is that the method of Pt coating after alumina sandblasting is seen to significantly reduce the bacterial adhesion by 67% when compared to the sandblasted PEEK sample after 24 h immersion, implying better biocompatibility without changing the cell viability performance.